Immune infiltration of tumor microenvironment following immunotherapy for glioblastoma multiforme. Issue 11 (2nd November 2017) - Sokratous, Giannis; Polyzoidis, Stavros; Ashkan, Keyoumars
ABSTRACT: Autologous dentritic cell immunotherapy has been proven effective in treating tumors outside the central nervous system. Current evidence from phase I and II trials suggest a similar efficacy for central nervous system tumors as well and that an active immune response against these tumors can be generated. We aim to review the literature to identify the types of immune responses against gliomas found to be generated by dendritic cell vaccinations and the types of immune cells subsequently infiltrating the glioma microenvironment. A systematic review of the literature was performed by searching the online databases PubMEd, Google Scholar, and EMBASE with use of the keywords intratumoral, infiltration, lymphocytic, vaccination and gliomas. Seven studies reporting lymphocytic infiltration of gliomas microenvironment were identified. Three studies (42.8%) reported presence of tumor infiltrating lymphocytes in 50%, 50% and 28.6% of included patients respectively in the post–vaccination specimens that were not present in the pre–vaccination samples. The remaining 4 (57.2%) reported an up to 6-fold increase in the number of pre-existing lymphocytes following vaccination. Present data indicate that tumor infiltration by lymphocytes can be induced by dentritic cell immunotherapy and that this may positively affect clinical outcome. It still remains unclear which factors influence the above reaction and therefore prediction of response to treatment is still not possible.